1990
DOI: 10.1163/156853890x00492
|View full text |Cite
|
Sign up to set email alerts
|

Field body temperatures of the amphisbaenid lizard Blanus cinereus

Abstract: Abstract. Body temperatures of Blanus cinereus recorded in the field in central Spainwere positively correlated with corresponding substrate and air temperatures. Mean body temperature was 1.2°C higher than corresponding mean substrate temperature. Mean body temperature varied with time of day. Presence under stones during daylight hours was bimodal and seasonal variation was observed in body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Number (N), volume (in mm 3 ) (V), frequency (F), and importance value (VI) of the prey in the diet of Amphisbaena munoai Klappenbach, 1969 and Anops kingi Bell, 1833 in Escudo Sul-Rio-Grandense, southern Brazil (NIA, non-identified arthropods). (MARTÍN et al, 1990;LÓPEZ et al, 1998), and for a fossorial snake Atractus reticulatus Boulenger, 1885 in an area close to the area of the present study in southern Brazil (BALESTRIN et al, 2007). However, studies on the physiology and habits of each species, as well as on the specific conditions of the soil involved, would be necessary for a better assessment of this hypothesis.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Number (N), volume (in mm 3 ) (V), frequency (F), and importance value (VI) of the prey in the diet of Amphisbaena munoai Klappenbach, 1969 and Anops kingi Bell, 1833 in Escudo Sul-Rio-Grandense, southern Brazil (NIA, non-identified arthropods). (MARTÍN et al, 1990;LÓPEZ et al, 1998), and for a fossorial snake Atractus reticulatus Boulenger, 1885 in an area close to the area of the present study in southern Brazil (BALESTRIN et al, 2007). However, studies on the physiology and habits of each species, as well as on the specific conditions of the soil involved, would be necessary for a better assessment of this hypothesis.…”
Section: Discussionmentioning
confidence: 53%
“…However, areas under the influence of temperate climate seem to favor the study of some species due to the easy access to the animals in their environment, as mentioned for Blanus cinereus (Vandelli, 1797) in Europe (GIL et al 1993;LÓPEZ & MARTÍN, 1994LÓPEZ & SALVADOR, 1992LÓPEZ et al 1991LÓPEZ et al , 1998LÓPEZ et al , 2002MARTÍN et al 1990MARTÍN et al , 2000, and observed here for Amphisbaena munoai and Anops kingi in southern Brazil.…”
Section: Amphisbaena Munoai Anops Kingimentioning
confidence: 56%
See 1 more Smart Citation
“…The only other species of the Amphisbaenidae that has previously been studied, A. mertensi, presented an average body temperature of 21.4 °C (SD = 2.7, range = 15.5-26.0 °C, n = 52) (Abe 1984). Similarly, in studies with Trogonophis wiegmanni Kaup, 1830, the range was between 17.6 and 27.6 °C, and thermoregulation and microhabitat selection were confirmed (López et al 2002, Civantos et al 2003; in studies with Blanus cinereus, the range was 19.6-25.2 °C (Martín et al 1990), and selection of soil depth and rocks during the day was observed (Martín et al 1991, López et al 1998. Diplometopon zarudny Nikolsky, 1907, an amphisbaenid with nocturnal habits, has a similar average body temperature (26.4 °C) in Central Saudi Arabia (Al-Johany 1999).…”
Section: Discussionmentioning
confidence: 88%
“…These have shown that Amphisbaena mertensii Strauch, 1881 (Abe, 1984), Blanus cinereus (Vandelli, 1797) (Martín et al 1990, 1991, Gil et al 1993, López et al 1998, Diplometopon zarudny Nikolsky, 1907(Al-Johany 1999, and Trogonophis wiegmanni Kaup, 1830(Gatten and McClung 1981, López et al 2002, Civantos et al 2003 thermoregulate and select particular microhabitats. However, only one study has investigated the thermal biology of the family Amphisbaenidae Gray, 1825, which was conducted by Abe (1984) and determined the preferred temperature of A. mertensii Strauch, 1881 in Brazil under field and laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%